5(x-6)+8=7x-10

Simple and best practice solution for 5(x-6)+8=7x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-6)+8=7x-10 equation:


Simplifying
5(x + -6) + 8 = 7x + -10

Reorder the terms:
5(-6 + x) + 8 = 7x + -10
(-6 * 5 + x * 5) + 8 = 7x + -10
(-30 + 5x) + 8 = 7x + -10

Reorder the terms:
-30 + 8 + 5x = 7x + -10

Combine like terms: -30 + 8 = -22
-22 + 5x = 7x + -10

Reorder the terms:
-22 + 5x = -10 + 7x

Solving
-22 + 5x = -10 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-22 + 5x + -7x = -10 + 7x + -7x

Combine like terms: 5x + -7x = -2x
-22 + -2x = -10 + 7x + -7x

Combine like terms: 7x + -7x = 0
-22 + -2x = -10 + 0
-22 + -2x = -10

Add '22' to each side of the equation.
-22 + 22 + -2x = -10 + 22

Combine like terms: -22 + 22 = 0
0 + -2x = -10 + 22
-2x = -10 + 22

Combine like terms: -10 + 22 = 12
-2x = 12

Divide each side by '-2'.
x = -6

Simplifying
x = -6

See similar equations:

| 185-5x=31x+21 | | 2k+5=12 | | 0=(-(x+4)(x+4))-7 | | 40+14y=-20-8y-6 | | 7z+4=-5z-2 | | -12=3(2n-10) | | 5y-3x+2y-4x= | | 4x-6=-31 | | -3y+2x= | | 7x+-12=2 | | 30x-25=50-20x | | -8d-(-2d)-6d= | | 16-x+2=23 | | 15b-24b= | | 888x=111 | | 7t+4t= | | N=zx-d | | 6rs+5r+8s-rs-r-s= | | 6-5j=-94 | | -0.5x+10=1.5x-5 | | -(5x+12)=12 | | -j+4k+jk-5jk+5j= | | 12x^2+5x-2x=0 | | .83+3j=-.67 | | 10y-4y= | | 20x-5=7+18x | | -8n+4(1+5n)=-6n+-14 | | s=4s-6 | | -0.9x+xy-0.8y+2y= | | 100x^2-4=0 | | 7=-56w | | c=38.34+0.50x |

Equations solver categories